(untitled) (Research, Society and Development, 2021)
This study aims to report a one-session endodontic treatment of a patient with chronic Non-progressive encephalopathy (CNPE). A patient with CNPE attended our postgraduate clinic for patients with special needs. During the anamnesis, the patient’s brother, who is his legal representative, reported discomfort with the esthetics of the patient’s anterior tooth and that the patient felt discomfort when touching the same dental element. After detailed anamnesis and elaboration of the treatment plan, endodontic treatment of element 11 (upper right central incisor) and coronary reconstruction were performed. Taking care of patients with cerebral palsy is still a challenge in dentistry. This is because care has to be taken when carrying out necessary interventions in these patients. This treatment aims at the positive resolution of their pathological condition and well-being. The possibility of endodontic treatment in a single session makes treatment more humane and less mutilating.